Effect of Feeding Different Levels of Rice Distillers Dried Grains with Soluble (RDDGS) on Performance of Broiler - Singh, Niharika; Dubey, Meenu; Doneria, Raina; Gendley, M. K.; Dinani, O. P.; Ramteke, R. C. (Indian Journal of Animal Nutrition, 2020)
Rice distillers dried grains with solubles (DDGS) is a co-product of rice-based ethanol production that can be a valuable source of energy, digestible amino acids, and available phosphorus in poultry feeds. Thus the present study was conducted for 5 weeks to study the effect of different dietary inclusion levels of rice DDGS on performance of broiler chickens. The diets were prepared using conventional feed ingredients: maize, deoiled soybean cakes, soy oil, rice DDGS and premixes containingtrace minerals and vitamins. The average body weight of chicks at the end of pre starter and starter phase was significantly (P<0.05) high in birds fed diet with 10 and 15% rice DDGS as compared to control, however at 35 d the difference in body weight was not significant amongst the group.Â No significant effect of rice DDGS inclusion on weekly and cumulative feed intake was observed. The cumulativeFCR upto 3 week was significantly (P<0.05) better in all the treatment groups irrespective of level of rice DDGS,however at the endof experiment the difference amongst the group was not significant. No significant effect of different dietary inclusion levels of rice DDGS on metabolizability of DM, CP and EE was observed. The N and Ca balance also did not vary significantly howeverthe P balance was significantly (P<0.05) high in all the treatment groups irrespective of level of rice DDGS. Birds fed diet with 10% DDGS gave best response in terms of net profit per kilogram of body weight. It is therefore recommended to include rice DDGS up to 10% level in broiler feed.